Polyhydride CeH9 with an atomic-like hydrogen clathrate structure - Xin Li (Nature Portfolio, 2019)
Obtainment of hydrogen-rich metal hydrides that are high-temperature superconductors has been demonstrated under very high pressure, but is still largely unexplored. Here the authors synthesize CeH9, with a structure related to solid metallic hydrogen, at relatively low pressure and without need for heating.